Study on Influencing Factors of Semen Quality in Fertile Men - Wang, Ning; Gu, Haike; Gao, Yiyuan; Li, Xiaoyan; Yu, Ge; Lv, Fang; Shi, Cuige; Wang, Shangming; Song, Meifang; Zhang, Shucheng (Frontiers in Physiology, 2022)
Objective: To establish a system for evaluation of semen quality in fertile men by factor analysis (FA). Methods: The FA method was used to analyze five sperm test indicators for fertile men (sperm pH, sperm motility, sperm progressive motility, semen density, and total sperm number) to determine the evaluation standard of semen quality. Pearson analysis was adopted for correlation testing. Results: The comprehensive score formula for semen quality of normal fertile men was as follows: comprehensive score of semen quality = (0.38272 F1 + 0.36359 F2 + 0.20018 F3) / 94.699. Across the whole fertile population, semen quality was found to be correlated with abstinence period, age of first spermatorrhea, and frequency of intercourse. Smoking, drinking, and place of residence were correlated with semen quality in the high semen quality population. In the population with medium semen quality, only the abstinence period was associated with semen quality. Conclusion: It is feasible to evaluate the semen quality of fertile men using the FA method. The comprehensive indicators of semen volume, sperm motility, and semen pH can be used as evaluative measures. Across the whole fertile population, the abstinence period and age of first spermatorrhea were correlated with semen quality. In the high semen quality population, smoking and drinking were negatively correlated with semen quality, and participants living in rural areas had better semen quality.